2022
DOI: 10.3390/min12020172
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-Based HR-Fluorescence and Mineralogical Mapping of the Initial Growth Stages of Polynesian Cultivated Pearls Disprove the ‘Reversed Shell’ Concept

Abstract: In a series of Polynesian pearls collected after short cultivation periods, early post-grafting mineral deposits were characterized by high resolution synchrotron-based X-ray fluorescence with unprecedented accuracy. Morphological patterns and elemental composition are correlated through simultaneous imaging processes. Evidence that aragonite and calcite occur in neighboring units during the earliest biomineralization stages reveals that the grafting process can result in a greater degradation than usually adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A previous study of the initial stages of calcite mineralization following metamorphosis [26] concluded that the development of the outer shell layer involves the sequential deposition of calcite and secretion cycles under continuous biological control. This is evident from the distribution of organic components during each step.…”
Section: Improving Understanding Of the Calcite Deposition Cycle In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of the initial stages of calcite mineralization following metamorphosis [26] concluded that the development of the outer shell layer involves the sequential deposition of calcite and secretion cycles under continuous biological control. This is evident from the distribution of organic components during each step.…”
Section: Improving Understanding Of the Calcite Deposition Cycle In T...mentioning
confidence: 99%
“…Additional information was obtained using a synchrotron-based instrument that combines high-resolution observation with crystallographic characterization. It was established that, in the earliest developmental stages, calcite and aragonite units crystallized simultaneously in the same growth layer [26].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The study of pearl formation and structure frequently involves imaging methods, with Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) being fairly common 2 – 5 . While these methods provide precise microstructural insights and aid in characterizing the formation and various deposits (calcite, aragonite) within pearls, they can be destructive to the pearl or financially prohibitive, limiting their widespread applicability.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the spots can vary depending on the technique used and has an impact on element quantification [ 29 ]. To analyse elements at the microscale, synchrotron X-ray fluorescence (XRF) is a promising method for producing fine-scale 2D elemental maps and can simultaneously produce multi-element maps of biomineralized structures [ 7 , 29 , 30 , 31 , 32 ]. XRF maps allow studying element incorporation dynamics throughout the otolith at a fine scale (presently down to 0.5 μm) [ 7 , 9 ], even for elements present at low concentrations (lower limit of detection: 1–10 ppm; see [ 33 ]).…”
Section: Introductionmentioning
confidence: 99%